The Role of Education Politics as a Foundation in Developing Curriculum and Educational Techniques in Indonesia - Khairul Anwar; Sesti Novalina; Kasful Anwar; Lias Hasibuan; Dewi Suryani (STAI Hubbulwathan Duri, 2021)
This research aims to explore the political role of education in Indonesia and the problems encountered in its implementation and solutions to overcome. Close relationship Politics and education exist in a mutually related system in its implementation for improving the quality of education. Educators have always embraced politics because the educational process can provide value and contribute to political development. Having a high understanding of education politics is expected to contribute to controlling the direction of educational activities in Indonesia. The literature research method was used to obtain references related to the required data that is analyzed. It can be concluded that political viewpoint refers to the relationship between politics and government policies due to Indonesia's educational systems, strategies, and techniques. Various regulations, decrees, rules, administrative actions in education are part of the evidence of the political role of policies for education. Another view of politics is politics as a process, how the political performance takes place. This approach is more complex in concept and requires understanding how government processes work and how human behavior affects all these processes as a culture.